CB2R Deficiency Exacerbates Imiquimod-Induced Psoriasiform Dermatitis and Itch Through the Neuro-Immune Pathway - Li, Li; Liu, Xin; Ge, Wenqiang; Chen, Chao; Huang, Yuqiong; Jin, Zilin; Zhan, Muouyang; Duan, Xiaoru; Liu, Xinxin; Kong, Yi; Jiang, Jian; Li, Xuemei; et al. (Frontiers in Pharmacology, 2022)
Background: Cannabinoid receptor 2 (CB2R) is a potential target for anti-inflammatory and pain therapeutics given its significant immunomodulatory and analgesic effects. However, the role of CB2R in imiquimod (IMQ)-induced psoriasiform dermatitis (PsD) and itch is poorly understood. Objective: To investigate the function and mechanism of CB2R in PsD and itch in mice. Methods: Following daily treatment with topical IMQ cream for 5-7 consecutive days in C56BL/6 wild-type (WT) and CB2R gene knockout (KO) mice, we assessed the Psoriasis Area and Severity Index (PASI) scores and the scratch bouts every day, and hematoxylin and eosin (H&E) staining, toluidine blue staining were used to observe the histological changes. mRNA levels were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Protein levels were detected by western blotting (WB), immunohistochemistry (IHC), immunofluorescence (IF) and cytometric bead array (CBA). Flow cytometry (FCM) was used to examine the proportion of Th17/Treg cells. Results: We found that CB2R expression levels were increased in mice with psoriasis. Compared with WT mice, CB2R deficiency exacerbated IMQ-induced PsD and scratching bouts and upregulated the expression of proinflammatory cytokines by increasing the infiltration of CD4+ T cells and the Th17/Treg ratio. Obvious proliferation and prolongation of nerve fibers and high expression of nerve growth factor (NGF) were observed in PsD and CB2R KO mice. Pretreatment with the CB2R agonist, JWH-133 significantly reversed inflammation and scratching bouts. CB2R didn’t participate in the induction of itch in psoriasis by regulating the expression of IL-31, TSLP and mast cells in mouse skins. Conclusion: Our results demonstrate that CB2R plays a pivotal role in the pathophysiology of psoriasis, providing a new potential target for anti-inflammatory and antipruritic drugs.